Analysis of genetic diversity and population structure of Magnaporthe grisea, the causal agent of foxtail millet blast using microsatellites - Dhivya,Manimozhi; Senthilraja,Govindasamy; Tharmalingam,Nagendran; Harish,Sankarasubramanian; Saravanakumari,Kalaiselvan; Anand,Theerthagiri; Thiruvudainambi,Sundararajan (PeerJ, 2023)
Foxtail millet blast caused by Magnaporthe grisea is becoming a severe problem in foxtail millet growing regions of India. The genetic diversity and population structure of foxtail millet infecting M. grisea is crucial for developing effective management strategies, such as breeding blast-resistant cultivars. We analyzed thirty-two M. grisea isolates from ten foxtail millet-growing districts in Tamil Nadu, India for genetic diversity using twenty-nine microsatellite or simple sequence repeat (SSR) markers. A total of 103 alleles were identified with a mean of 3.55 alleles/locus. Gene diversity ranged from 0.170 to 0.717, while major allelic frequencies ranged from 0.344 to 0.906. The polymorphism information content (PIC) ranged from 0.155 to 0.680, with a mean value of 0.465. Population structure analysis of the genomic data sets revealed two major populations (SP1 and SP2) with different levels of ancestral admixture among the 32 blast isolates. Phylogenetic analysis classified the isolates into three major clusters. Analysis of molecular variance (AMOVA) showed high genetic variation among individuals and less among populations. Principal Coordinate Analysis (PCoA) revealed 27.16% genetic variation among populations. The present study provides the first report on the genetic diversity and population structure of the foxtail millet-infecting M. grisea population in Tamil Nadu, which could be useful for the development of blast-resistant foxtail millet cultivars.
Keywords: Foxtail millet; Diversity; Population structure; Microsatellites; Phylogenetics; Blast